A phenomenology study of clinicians' perspectives on dissociation while working with traumatised children in the South African context. - Van, Der Walt Ruth (Department of Social Development, 2023)
The statics of children experiencing trauma is extremely high in South Africa, with the expectation of 1 in 3 children experiencing sexual abuse before eighteen years of age. Trauma is defined as experiences which overwhelm the internal resources of a child and changes their perception of their lives and environment. Dissociation is a protective mechanism functioning to shield the conscious from trauma by preventing the processing of these experiences. The researcher was interested in whether dissociation is a phenomenon which is present in children living in South Africa who have a history of trauma. To determine this, the researcher applied a qualitative approach and phenomenological design to the research. The researcher used a purposive sample of sixteen clinicians practicing in the Western Cape metropole, to determine whether dissociation is present and how it appears in children who have a history of trauma. The findings showed that dissociation was found to be present in children who have experienced trauma living in the Western Cape metropole. Furthermore, the data indicated that between 60 and 80% of children who had experienced trauma present with dissociation. The dissociative symptoms and features identified were misbehaviour and daydreaming. Predisposing and precipitating factors were found to be risk factors for the development of dissociation after a trauma is experienced. These factors were the younger the child when the trauma happened the more likely the development of dissociation. Secondly, the type of trauma experienced and a disorganised attachment style with the caregiver. A protective factor identified was the presence of a secure attachment between the child and caregiver before trauma is experienced. The therapeutic treatment of dissociation was described as holistic in nature by involving the child's caregivers. The main therapy used by the participants with children who present with dissociation were based on play therapy techniques and recreating a sense of safety for the child needs to be a primary goal of treatment. Recommendations for further study was given due to the impression of limited understanding and knowledge of dissociation. The findings emphasised the importance of the caregiver being involved in the therapeutic process and therefore it is recommended that clinicians who render therapeutic services to children include the caregivers in the therapeutic process. The data showed that trauma informed polices and interventions need to be developed to further assist children who have a history of trauma and present with dissociation.